Consumer Demand and Unobservable Product Attributes - Leif Brubakk; John K. Dagsvik (Statistics Norway, Research Department, 1998)
Traditional approaches to consumer demand modelling ignores the problem associated with product heterogeneity where important product characteristics are latent. The point of departure in the present study is a particular framework developed in Dagsvik (1996a,b) and Dagsvik et al. (1998). In this approach the consumer is assumed to make his choice from a discrete set of product variants. The resulting model has the form of a modified conventional demand system, where the modification consists in replacing the standard price indexes by a indexes which are derived from underlying behavioral assumptions. The empirical application is based on a sample of Norwegian micro data market prices and household consumption.
Keywords: C31; C43; D12; 330; Consumer demand; Differentiated products; Unobserved product heterogeneity